Isolation and characterization of a cDNA clone for the gamma subunit of bovine retinal transducin. - Hurley, J B (1984)
We have isolated and characterized a cDNA clone that encodes the gamma subunit of transducin, the guanine nucleotide binding regulatory protein found in vertebrate photoreceptors. The gamma subunit was separated from the alpha and beta subunits of transducin and purified to homogeneity by reversed-phase high performance liquid chromatography. The sequence of the first 45 amino acids at the amino terminus of this polypeptide was then determined by automated Edman degradation. Oligodeoxynucleotide probes corresponding to two nonoverlapping regions of this sequence were synthesized and then used to screen a bovine retinal cDNA library. One probe, T gamma 1, was a mixture of 32 different heptadecamers complementary to all possible mRNA sequences that could encode a portion of the T gamma sequence; the other probe, T gamma 2, was a mixture of 128 different heptadecamers. Thirteen clones that hybridized with T gamma 1 were selected. Only one of these had an insert that also hybridized with T gamma 2. The DNA sequence of this insert encodes a 73-amino acid polypeptide that corresponds to the transducin gamma subunit on the basis of amino-terminal sequence, amino acid composition, and carboxyl-terminal sequence. The molecular weight of the mature gamma subunit is 8400. It appears to be synthesized as a discrete polypeptide and not as a domain of a larger precursor polyprotein. The transducin gamma subunit is very hydrophilic and acidic; it has 19 acidic and 11 basic amino acids as well as three cysteine residues. Furthermore, significant homology was found in comparisons of the nucleic acid sequence corresponding to the carboxyl terminus of the gamma transducin transcript with the sequences corresponding to the carboxyl terminus of ras oncogene products, suggesting a possible ancestral relationship between these genes.